Predictive criteria of severe cases in COVID‐19 patients of early stage: A retrospective observational study. Issue 10 (6th September 2020) - Gao, Jinrui; Huang, Xiu; Gu, Haibo; Lou, Lingyun; Xu, Zhihao
Abstract: Background: Patients with coronavirus disease 2019 (COVID‐19) often suffer sudden deterioration of disease around 1‐2 weeks after onset. Once the disease progressed to severe phase, clinical prognosis of patients will significantly deteriorate. Methods: This was a multicenter retrospective study on patients of all adult inpatients (≥18 years old) from Tianyou Hospital (Wuhan, China) and the Fourth Affiliated Hospital, Zhejiang University School of Medicine. All 139 patients had laboratory‐confirmed COVID‐19 in their early stage, which is defined as within 7 days of clinical symptoms. Univariate and multivariate logistic regression models were used to determine the predictive factors in the early detection of patients who may subsequently develop into severe cases. Results: Multivariable logistic regression analysis showed that the higher level of hypersensitivity C‐reactive protein (OR = 4.77, 95% CI:1.92‐11.87, P  = .001), elevated alanine aminotransferase (OR = 6.87, 95%CI:1.56‐30.21, P  = .011), and chronic comorbidities (OR = 11.48, 95% CI:4.44‐29.66, P  < .001) are the determining risk factors for the progression into severe pneumonia in COVID‐19 patients. Conclusion: Early COVID‐19 patients with chronic comorbidities, elevated hs‐CRP or elevated ALT are significantly more likely to develop severe pneumonia as the disease progresses. These risk factors may facilitate the early diagnosis of critical patients in clinical practice. Abstract : Early COVID‐19 patients with chronic comorbidities, elevated hs‐CRP or increased ALT are significantly more likely to develop severe pneumonia as disease progresses